2019
DOI: 10.1021/acs.organomet.8b00896
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Double-Decker Silsesquioxanes from Substituted Difluorosilane

Abstract: A novel synthetic method for the construction of a double-decker silsesquioxane from fluorosilanes was developed. Phenyl-substituted double-decker silsesquioxane was prepared under mild conditions by coupling difluorodiphenylsilane and a tetrasiloxanolate precursor. A similar reaction was performed using difluorovinylsilane, and a divinyl double-decker silsesquioxane was obtained. The one-step reaction of a functional difluorosilane containing an aminopropyl group afforded a novel double-decker silsesquioxane … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 58 publications
3
17
0
Order By: Relevance
“…unique physical and chemical properties are widely used in material science. [43,44] Also this time (the Si-O-Si bond formation), there are several established methods, which can be carried out in both stoichiometric [43,45,46] or catalytic manner. [47][48][49][50][51][52][53][54][55][56][57][58][59][60] To sum up, the vast majority of known O-silylation strategies is presented on Figure 1, including their main benefits and drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…unique physical and chemical properties are widely used in material science. [43,44] Also this time (the Si-O-Si bond formation), there are several established methods, which can be carried out in both stoichiometric [43,45,46] or catalytic manner. [47][48][49][50][51][52][53][54][55][56][57][58][59][60] To sum up, the vast majority of known O-silylation strategies is presented on Figure 1, including their main benefits and drawbacks.…”
Section: Introductionmentioning
confidence: 99%
“…The temperature of 5 wt % weight loss (T5%) and the char residue yield at 800 °C suggested good flame retardancy of PC/ABS containing B-POSS. With a special substituted difluorosilane as a precursor, Tanaka et al [100] reported a substituted difluorosilane prepared from the reaction between BF3•Et2O and siloxanolate in the synthesis of an amide product. The difluorosilane, bearing a vinyl-or BF3-complexed amino group, was used as the raw material to synthesize polycyclic silsesquioxanes under mild conditions.…”
Section: Other Bifunctional Possmentioning
confidence: 99%
“…Due to the simplicity of materials processing, good solubility, high chain regularity, and POSS content in the hybrids [89,105], more attention has been paid to B-POSS-containing linear composite materials because of the specific nanostructure, hydrophobic core, functionalization, flame retardance, optical transparency, and low thermal conductivity. With a special substituted difluorosilane as a precursor, Tanaka et al [100] reported a substituted difluorosilane prepared from the reaction between BF 3 •Et 2 O and siloxanolate in the synthesis of an amide product. The difluorosilane, bearing a vinyl-or BF 3 -complexed amino group, was used as the raw material to synthesize polycyclic silsesquioxanes under mild conditions.…”
Section: Polymer Composites Containing B-possmentioning
confidence: 99%
“…Reacting tetrasilanol of double-decker shaped octaphenyl silsesquioxane DDSQ(OH) 4 with an appropriate quantity of dichlorosilanes (RR'SiCl 2 ) or difluorosilanes (RR'SiF 2 ) can result in a fully condensed structure (DDSQ-2(RR')) as observed in Scheme 1 [1][2][3][4][5][6][7][8][9]. These compounds have been used to form hybrid polymers with silsesquioxane as a part of the backbone [3,6,10].…”
Section: Introductionmentioning
confidence: 99%